Chinese architecture [videorecording] - Hong, Mei; Beijing Television Productions Consulting Network diagram filming; Foreign cultural centers producer; China. Ministry of Culture. Bureau for External Cultural Relations (Beijing : Beijing Wangtu Film & TV Production Consulting Co.,Ltd.)
"In material culture, constructions can exactly reflect aesthetic perception and cultural tradition of a country and nation. In retrospect of the original genesis of magnificent constructions, we have discovered the particular concept of the "home" as follows: The homes for civilians and imperial families, homes for mentalities and emotions, and homes for religions and faiths ... These homes have experienced changes of thousands of years in history. They have shown their colorful varieties with the nourishments of national traditions and customs in different geographical environments. They not only represent outstanding achievements in architecture and aesthetics, but also embody local cultural features and philosophical thoughts of the time in those building materials. Aesthetic enlightenment derived from constructions is handed down in details from generation to generation"--Container